Breaking the Learners’ Social Barriers and Improving their English Learning Process through the Use of Cooperative Learning Strategies (2022)
ABSTRACT: This action research project aimed to analyze how cooperative learning strategies affect fourth-grade students’ English learning process at a public institution in Medellín, Colombia. The participants were 26 Colombian and 2 Ecuadorian students whose ages ranged between 8 and 10. The actions of this project were divided into two main parts: the cooperative learning strategies and the social skill development activities. The data was collected through journal entries, students’ class reflections, students’ drawings, students’ surveys, and advisor’s visit comments. Findings suggest that this action plan: a) had a positive impact on students’ perception of cooperation, b) achieved the five elements of cooperation according to Johnson (2009), c) benefited students’ English learning, cooperative work knowledge, and social skill development, d) faced some difficulties with classroom situations in terms of students’ relationships, and a student condition, e) created a fun school scenario for learning the English language, and f) developed some students’ social skills concerning social interaction, social communication, emotional communication, and the creation of consensus.